Bach In Auschwitz - Daëron, Michel (Les Films D'ici ; Filao Films ; Scarabee Films Producties Nederland, 1995)
Duration: 01:45:00 The tale of Auschwitz's bizarre all-female orchestra. This film is a documentary - a series of interviews and filmed episodes - of the surviving members of the Auschwitz orchestra. They tell their stories, and their memories of performances, and tell of their horror at being used by the Nazis - forced to play for the entertainment of their tormentors as their friends and relatives were led to the gas chambers. Many of the women who played in the group are interviewed.